Bacteriological and Polycyclic Aromatic Hydrocarbon Accumulation in Mangrove Oyster (Crassostrea tulipa) from Douglas Creek, Nigeria - Eduok, S.I.; Ebong, G.A.; Udoinyang, E.P.; Njoku, J.N.; Eyen, E.A. (Pakistan Journal of Nutrition, 2009)
Bacteriological density and polycyclic aromatic hydrocarbon concentrations were determined in the brackish surface water and mangrove oyster (Crassostrea tulipa) from Douglas creek, Nigeria. Total Heterotrophic Bacteria (THBC), Total Vibrio (TVC) and Total Coliform (TCC) counts ranged from 8.8 x 104 - 10.8 x 104 cfu/ml, 2.1 x 104 - 3.8 x 104 cfu/ml and 5.2 x 104 - 7.2 x 104 cfu/ml in water whereas THBC, TVC, TCC in the mangrove oyster ranged from 12.5 x 106 - 17.9 x 106 cfu/g, 3.9 x 105 - 5.8 x 105 cfu/g and 8.9 x 105 - 9.7 x 105 cfu/g. The microbial groups in the water and oyster exhibited varying correlations with r-values (p = 0.05) ranging from -0.3767 to 0.7209. The bacterial isolates were Staphylococcus saprophyticus, Aerobacter aerogenes, Citrobacter sp, Bacillus cereus, Streptococcus sp, Vibrio parahaemolyticus, Vibrio cholerae, Pseudomonas putida, Pseudomonas aeruginosa, Escherichia coli, Enterococcus faecalis and Serratia marcescens, Acinetobacter iwoffii, Chromatium sp, Micrococcus sedentarius, Listeria monocytogenes and Klebsiella pneumoniae. The individual PAH accumulated by the mangrove oyster ranged from 0.02-3.56 mg/kg against background surface water PAH concentration which ranged from 0.02 - 1.00 mg/l. Total PAH concentration in brackish surface water and mangrove oyster tissue was 7.51 mg/l and 11.96 mg/kg respectively. The Bioconcentration Factor (BFC) of the individual PAH in the mangrove oyster ranged from 0.51 [benzo (b) fluoranthene] to 17.8 [dibenzo (a,h) anthracene]. The microbial isolates are of health significance and PAH concentration in the mangrove oyster could biomagnify along the food chain with adverse toxicological effects on ardent consumers of the biota. The mangrove oyster (Crassostrea tulipa) could be used as a biomarker of bacterial and PAH contamination of the mangrove ecosystem.